2006
DOI: 10.1111/j.1365-2958.2006.05123.x
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical involvement of various GGDEF domain proteins in rdar morphotype development of Salmonella enterica serovar Typhimurium

Abstract: SummaryGGDEF and EAL domain proteins are involved in the turnover of the novel secondary messenger cyclicdi(3 ¢AE 5 ¢ )-guanylic acid (c-di-GMP) in many bacteria. In this work the role of the 12 GGDEF domain proteins encoded by the Salmonella enterica serovar Typhimurium ( S. Typhimurium) chromosome in rdar morphotype development was investigated. Previously, it was shown that the GGDEF domain protein AdrA activated the biosynthesis of cellulose by production of c-di-GMP. Enhancement of the c-di-GMP levels by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
212
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(240 citation statements)
references
References 47 publications
15
212
0
5
Order By: Relevance
“…More specifically, the c-di-GMP phosphodiesterase FimX is involved in the assembly of Tfp type IV pili, which are required for twitching motility, biofilm formation, and adherence of Pseudomonas (52). In addition, increased c-di-GMP levels in S. typhimurium are associated with increased curli synthesis (53). Our work revealed yet another virulence factor, type 1 pili, whose expression is regulated via a c-di-GMP-dependent pathway.…”
Section: Discussionmentioning
confidence: 78%
“…More specifically, the c-di-GMP phosphodiesterase FimX is involved in the assembly of Tfp type IV pili, which are required for twitching motility, biofilm formation, and adherence of Pseudomonas (52). In addition, increased c-di-GMP levels in S. typhimurium are associated with increased curli synthesis (53). Our work revealed yet another virulence factor, type 1 pili, whose expression is regulated via a c-di-GMP-dependent pathway.…”
Section: Discussionmentioning
confidence: 78%
“…The crude product (11% cyclization yield) was purified by reversedphase HPLC and characterized by MALDI-TOF MS, as discussed later. Reversed-phase HPLC analyses were carried out on Teknokroma C18 columns (10 m, 250 ϫ 4.6 mm), using a multistep gradient of 0.05 M aq ammonium acetate, pH 7.0, and ACN/H 2O (1:1) at 1 ml/min (12,31). MALDI-TOF MS analysis (Voyager-DERP, Applied Biosystems) was performed in the negative mode using ammonium citrate and either ␣-cyano-hydroxycinnamic acid or trihydroxyacetophenone matrices: m/z 688.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have concluded that c-di-GMP functions via high specificity based on the observation that the intracellular concentration of c-di-GMP does not directly correlate with phenotypic expression (14)(15)(16)(17), an observation inconsistent with a low-specificity system. These studies relied on mutagenesis of respective DGCs.…”
mentioning
confidence: 99%